Luciferase-dependent oxygen consumption by bioluminescent vibrios. - Makemson, J C (1986)
Oxygen uptake due to luciferase in two luminous Vibrio species was estimated in vivo by utilizing inhibitors having specificities for luciferase (decanol) and cytochromes (cyanide). Cyanide titration of respiration revealed a component of oxygen uptake less sensitive to cyanide which was completely inhibitable by low concentrations of decanol. From this it was estimated that in vivo luciferase is responsible for less than 12% (Vibrio harveyi) or 20% (Vibrio fischeri) of the total respiration. From these data in vivo bioluminescent quantum yields are estimated to be not lower than 1.7 and 2.6%, respectively.